(untitled) (Research, Society and Development, 2021)
The management of patients with neurodegenerative conditions such as Alzheimer’s disease presents a challenge in promoting oral health, which is mainly linked to the motor and cognitive limitations that these individuals have, making them susceptible to the development of a series of oral diseases, such as oral myiasis. The presence of larvae in the oral cavity in patients with Alzheimer’s disease seems to be related to poor oral hygiene condition, to the long periods that the patient remains immobile and with the mouth ajar, facilitating the deposition of eggs. Therefore, this study aimed to report a clinical experience of a patient with Alzheimer’s disease in an advanced stage and with manifestation of oral myiasis on the oral floor, vestibule bottom and inserted gum. The 81-year-old patient was debilitated, bedridden, unable to perform his activities alone, was taken to the emergency room by his caregiver, who reported having noticed the presence of larvae in the oral cavity. The patient was hospitalized and immediately administered Ivermectin, ceftriaxone and clindamycin. On the second day of hospitalization, he presented a systemic worsening due to bronchoaspiration, requiring immediate removal of the larvae under local anesthesia. Only after significant improvement in the general condition, thorough surgery was performed to debridement of the injured areas and remnants of larvae. After hospital discharge with 2-month follow-up, the patient did not have any complications related to his oral health, demonstrating that periodic follow-up to debilitated patients is an important tool for preventing opportunistic manifestations such as oral myiasis.